Growth And Development Of Craft Tourism Services In Tamilnadu - BASKARAN, DR.B.; MANIKANDAN, K. (The journal of contemporary issues in business and government, 2021)
India is one of the leading suppliers of handicrafts in the world market. Among Indian states, Tamil Nadu is a place for its rich history of culture &tradition in the Handicrafts Industry and occupies an important place in this sector. Tourisms play a vital role in promoting goodwill among the people and social economic development of the country. Tourism as an industry earns large foreign exchange reserves and creates direct and indirect employment opportunities to very large sections of society. Besides promoting handicrafts and fine arts of a nation, it helps in preserving the nature’s beauty, cultural heritage of the land, and strengthens the process of national integration and universal brotherhood. This study is to highlights development of craft tourism services in Thanjavur district Tamil Nadu.